Do algorithms extend the community of knowledge? - Kim, Hyoseok; Sloman, Steven (SSRN Electronic Journal, 2025)
Keywords: Cognition; Computational sociology; Key (lock); Perception; dept.mrk

Are charitable gifts truly appreciated by the recipients who requested them? Impact of gift type and amount on recipients’ appreciation - Kang, In-Hye; Kim, Hyoseok (Journal of Business Research, 2025)
• For requested gifts during rite-of-passage occasions, appreciation for charitable vs. recipient-benefiting gifts depends on gift amount. • For low gift amounts, recipients appreciate charitable gifts more than recipient-benefiting gifts. • For moderate to high gift amounts, appreciation is similar between charitable and recipient-benefiting gifts. • In distant (vs. close) giver-recipient relationships, the effect of gift type on appreciation for low amounts is attenuated. • When gifts are not requested, recipients appreciate charitable gifts less than recipient-benefiting gifts. Requests for charitable cash gifts during rite-of-passage occasions (e.g., weddings) are becoming increasingly common. This research examines whether recipients’ appreciation differs depending on whether a requested cash gift is charitable (e.g., donating to support people in need) or recipient-benefiting (e.g., renovating the recipient’s kitchen). Across five studies, we find that the effect of the gift type on appreciation is moderated by the gift amount. For low amounts, recipients appreciate charitable gifts more than recipient-benefiting gifts. However, for moderate and high amounts, appreciation is similar across gift types. This effect is mediated by the recipients’ perception of whether the gift amount meets their expectations and their subsequent perception of thoughtfulness. Consistent with our mechanism, in distant giver-recipient relationships, the effect of the gift type on appreciation for low amounts is attenuated. When gifts are not requested, recipients appreciate charitable gifts less than recipient-benefiting gifts.
Keywords: Advertising; Business; Charitable gifts; Charitable giving; Conflict of interest; Donation; Economic growth; Economics; Finance; Gift appreciation; Gift giving; Gift price; Gift-giving; Marketing; Psychology; Social psychology; dept.mrk; peer-reviewed